The Role of Intersectionality and Context in Measuring Gender-Based Violence in Universities and Research-Performing Organizations in Europe for the Development of Inclusive Structural Interventions - Humbert, Anne Laure (Violence against women, 2025)
The aim of the article is to discuss how thinking about gender-based violence intersectionally and in context can not only enrich our understanding but also lead to transformative change in organizations. The article argues that to better understand gender-based violence in universities and research institutions, analyses need to be intersectional and contextual. Such approaches go beyond binary understandings of gender and narrow legalistic definitions of gender-based violence. The article reflects on how to operationalize this to derive starting points for intersectional categories to consider and contextual factors to measure at micro-, meso-, and macro-levels. It concludes that a multilevel intersectional analysis leads to more nuanced knowledge on experiences of gender-based violence and is, therefore, better equipped to inform the development of measures to eradicate the problem in an inclusive way.